Dictionary Speech Assistant to Improve Students Pronunciation - Susanto, Agnesia Stefanny; Ardini, Sukma Nur; Sukmaningrum, Rahmawati (Allure Journal, 2024)
Non-native students often experience difficulty to learn pronunciation which then affects their speaking ability. On the other hand, proper communication requires proper pronunciation as well. However, todays technological advancement provides an alternative to aid pronunciation mastery, one of which is in the context of mobile-assisted language learning. This research investigated the effectiveness of Dictionary Speech Assistant in ELSA Speak Application to Improve Second Grade Students of SMP Negeri 6 Semarang Pronunciation Ability. The objective of this research was to find out the result of studentspronunciation ability before and after applying Dictionary Speech Assistant; as well as to find out whether there was any significant difference of studentsachievement in their pronunciation mastery before and after taught using this mobile application. Dictionary Speech Assistant is one of the features or tools in ELSA Speak Application. It is a pronunciation dictionary that facilitated by Automatic Speech Recognition which provides direct feedback. This research employs pre-experimental design involving 34 students as the research sample. The data was gained from pre-test and post-test. The instrument of this research were tests consisting of single-word and phrase test. Subsequently, the data was analyzed by using t-test formula in Microsoft SPSS software to find out the significant difference on studentspronunciation ability before and after applying Dictionary Speech Assistant. The result showed that Dictionary Speech Assistant effectively improves the students pronunciation ability. The main factor affecting this improvement was the studentsinterest in teaching learning process involving Dictionary Speech Assistant. The researchers concluded that Dictionary Speech Assistant is beneficial for students in learning pronunciation